Ultrasonic camera for finger ridge pattern imaging - BICZ, W.; BANASIAK, D.; BRUCIAK, P.; GUMIENNY, Z.; GUMULIŃSKI, S.; KOSZ, D.; KRYSIAK, A.; KUCZYŃSKI, W.; PLUTA, M.; RABIEJ, G. (Archives of Acoustics, 1998)
This paper describes the design of an ultrasonic camera with a resolution of 0.1 mm. The camera makes it possible to observe the near surface structures of solid objects and is suitable for finger ridge pattern imaging (i.e. a pattern reflected in the fingerprint). The device can be used for biometric identification of individuals (for access verification). It can also be employed for all other sorts of structures with ultrasonically detectable changes in the near surface structure, both natural and artificial ones (e.g. created for information recording). The paper describes the current version of the camera and the physical basis of its operation. Perspectives of further development of the device are also presented.